Supplementary Table S3 from Dysregulation and Epigenetic Reprogramming of NRF2 Signaling Axis Promote Acquisition of Cisplatin Resistance and Metastasis in Head and Neck Squamous Cell Carcinoma - Abdullah A. Osman (15056323) (2025)
Whole exome sequencing showing mutational status in the parental HN30-P versus HN30-R8 cisplatin resistant cell lines.